PENGELUARAN PEMERINTAH, AKUMULASI MODAL, PAJAK DAN EKSPOR TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA - Rini, Dyah Ayu Mustika; Yulistiyono, Herry (Universitas Nusantara PGRI Kediri, 2021)
This study aims to analyze the effect of government spending, capital accumulation, taxes and exports on economic growth in Indonesia. The research uses a quantitative approach. The data in this study are secondary data obtained from the World Bank. The data time series used is from 1976-2018. The analysis technique uses Ordinary Least Squares (OLS) with an Error Correction Model (ECM) approach. The results show that: (1) Government expenditure variables have a positive effect on Indonesia's economic growth. (2) The variable of capital accumulation has a positive effect on Indonesia's economic growth in the long term while in the short term it has no effect. (3) The tax variable has no effect on Indonesia's economic growth both in the long term and in the short term. (4) Export variables in the long term have no effect on Indonesia's economic growth and have an effect. (5) The variables of government spending, capital accumulation, taxes and exports together have an effect on economic growth in Indonesia. ECT variable of -0.260759 indicates adjustment to equilibrium conditions for 1 year 2 months